Volume 2A: Turbomachinery 2014
DOI: 10.1115/gt2014-25329
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Investigation on the Effect of Vortex Generator on Axial Compressor Performance

Abstract: The performance of the compressor blade is considerably influenced by secondary flow effects, like the cross flow on the end wall as well as corner flow separation between the wall and the blade. The present work is focused on the studying the effects of Vortex Generator (VG) on NASA Rotor 37 test case using Computational Fluid Dynamics (CFD). VG helps in controlling the inception of the stall by generating vortices and energizes the low momentum boundary layer flow which enhances the rotor performance. Three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…With the increasing x/c , the Cs values on the suction and pressure sides exhibited a downward trend and an upward trend, respectively, gradually converging close to 0 in the trailing edge direction (where x/c approaches 1), demonstrating a parabolic change as a whole. The analysis results indicate that the presence of a laminar separation bubble on the pressure side (where the inflow point nears the leading edge) because of high‐speed air flow and that Cs approached 0 here 51–54 . In addition, because the shear stress of the fluid wall was dominated by the flow velocity, the distance was longer and the flow velocity was higher on the suction side, resulting in a larger Cs.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…With the increasing x/c , the Cs values on the suction and pressure sides exhibited a downward trend and an upward trend, respectively, gradually converging close to 0 in the trailing edge direction (where x/c approaches 1), demonstrating a parabolic change as a whole. The analysis results indicate that the presence of a laminar separation bubble on the pressure side (where the inflow point nears the leading edge) because of high‐speed air flow and that Cs approached 0 here 51–54 . In addition, because the shear stress of the fluid wall was dominated by the flow velocity, the distance was longer and the flow velocity was higher on the suction side, resulting in a larger Cs.…”
Section: Resultsmentioning
confidence: 93%
“…pressure side (where the inflow point nears the leading edge) because of high-speed air flow and that C s approached 0 here. [51][52][53][54] In addition, because the shear stress of the fluid wall was dominated by the flow velocity, the distance was longer and the flow velocity was higher on the suction side, resulting in a larger C s . However, the distance was shorter, and the flow velocity was lower on the pressure side; C s was also smaller than that on the suction side.…”
Section: Shear Stress Coefficientmentioning
confidence: 99%
“…Optimal drag coefficient was obtained taking into account several parameters such as the VG height, the position from the leading edge and the aperture. The effects of VG attached at different locations and at various attack angles have been studied by Gopinathan et al (2015), Kumar et al (2016) and Agarwal et al (2016). They found that at small attack angles, the VG have insignificant effects with a small decrease in the lift force and a small increase in the drag force.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that maximum drag reduction of 12% and lift reduction of 60% were attained and further reduction achieved significantly through motorization of VG with respect to wind speed. Shubham Agarwal et al (2016) investigated the aerodynamic behavior on wing with the effect of VG location. The flow field measured on the wing with VG attached at various locations and angle attack varied.…”
Section: Introductionmentioning
confidence: 99%